Correlation of damage score in PTOA with changes in stress on cartilage in an ovine model. Issue 4 (December 2020) - Vakiel, Paris; Shekarforoush, Mehdi; Dennison, Christopher R.; Achari, Yamini; Muench, Gregory; Scott, Michael; Hart, David A.; Shrive, Nigel G.
Summary: Objective: There is a high risk of developing osteoarthritis (OA) following traumatic injury to the knee. Severe ligament injuries can disrupt the integrity of the multicomponent knee at both biological and biomechanical levels. We hypothesize changes in cartilages stresses could lead to tissue damage and development of OA. Design: The in-vivo gait kinematics of the stifle (knee) joint of four adult female ovine subjects were recorded prior to and at ten-and-twenty weeks following partial ACL-MCL transection. The subjects were sacrificed and the experimental joint from each subject was mounted on a parallel robotic system programmed with the kinematic findings. Ten custom-built Fibre Bragg Grating optic sensors were arranged to measure contact stresses on the surface of the tibial plateau articular cartilage. These sensors provide the first accurate stress measurements in a joint during gait replication using the previously recorded in-vivo kinematics. The relationship between the results obtained and observed focal damage was assessed. Results: The locations on the tibial plateaus that experienced the greatest change in contact stresses corresponded with the locations of focal damage development. No direct link was detected between individual animal differences in kinematics and variations in stress magnitudes or the development of focal cartilage damage. Conclusions: The findings highlight the importance of mechanical stress determinants in the integrated set point for the knee (with individual variation), and how injury-related stress changes correlate with development of PTOA.